The Relationship Between Consumption of Sweet Foods and Beverages and Physical Fitness Levels Among Adolescents - Silvi Puspitasari; Farida Nur Isnaeni (Universitas Negeri Semarang, 2026)
Adolescence is a critical transitional phase marked by significant physical development and changing dietary habits, including an increased preference for sugar-sweetened products. Excessive sugar consumption is theoretically linked to metabolic disturbances and muscle fatigue, which may negatively impact physical fitness. This study aims to investigate the relationship between sugar-sweetened intake and physical fitness levels among adolescents at Batik 1 Surakarta Senior High School. An observational study with a cross-sectional approach was conducted involving 91 adolescent students at Batik 1 Surakarta Senior High School, selected through simple random sampling. Sugar-sweetened intake, encompassing both foods and beverages, was assessed using a FFQ covering the past month. Physical fitness levels were measured using the Harvard Step Test to calculate the Physical Fitness Index (PFI). Data were analyzed using the Chi-Square test to identify significant correlations between variables, with a significance threshold of p < 0.05. The Chi-Square test results showed a p-value = 0,080 with an Odds Ratio (OR) of 2,375 (CI = 0,889-6,344), indicating no statistically significant relationship between the consumption of sweet foods and beverages and physical fitness levels among adolescents at Batik 1 Surakarta Senior High School. However, frequency distribution data revealed an interesting trend; the group of adolescents with infrequent sugar-sweetened intake had a higher proportion of those in the